Disharmonisasi Regulasi Internal: Studi Kasus Pelanggaran Hak pada Perjanjian Kerja Bersama (Pkb) PT Garuda Indonesia (Persero) TBK - Anna Rosliana; Muhamad Irayadi (HUMANIORUM, 2026)
Harmonious industrial relations are key to the operational stability of a company, especially for strategic State-Owned Enterprises (SOEs). However, PT Garuda Indonesia (Persero) Tbk frequently faces internal conflicts regarding the fulfillment of employee rights. This study aims to analyze the root causes of disharmony between internal regulations (management policies) and the Collective Labor Agreement (CLA), as well as the legal implications of violations of workers' normative rights. Using a qualitative research method with a socio- legal approach, data were collected through document studies of CLA manuscripts, company regulations, and literature related to industrial relations conflicts at Garuda Indonesia. Data analysis was conducted descriptively-analytically to dissect the phenomenon of managerial non-compliance with collective agreements. The results show that disharmony is rooted in corporate efficiency policies carried out unilaterally by overriding clauses in the CLA, particularly regarding allowances, welfare guarantees, and working hour management. These violations triggered a degradation of trust between the Employee Union and Management, leading to strike threats and legal lawsuits. Legally, the CLA holds a binding legal position similar to a law for the parties involved. Therefore, any internal policy that contradicts the CLA is null and void. The conclusion of this study emphasizes the need to strengthen the function of the Bipartite Cooperation Institution and financial transparency as conflict mitigation instruments to create a balance between the company's economic interests and the constitutional rights of workers.